2018
DOI: 10.1590/1982-0216201820210917
|View full text |Cite
|
Sign up to set email alerts
|

Tongue pressure and endurance in patients with Class II and Class III malocclusion

Abstract: Objective: to evaluate pressure and endurance exerted by the tongue and their association with malocclusion, gender and age in orthognathic surgery candidates. Method: a cross-sectional, descriptive observational study, performed with 34 subjects, i.e., 18 women and 16 men, in the average age 28.7 years, sorted by Angle’s classification. Self-reported complaint of tongue mobility and stomatognathic functions was assessed and the evaluation of tongue mobility carried out. Tongue pressure and endurance were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…With regard to age, the findings of this research showed lower pressure of the lips in older subjects. In the same vein, it was observed a decrease of pressure values with age in a study 34 that evaluated the tongue pressure with IOPI in subjects with malocclusion. In contrast, a sample of children in Class II has used a nozzle connected to a dynamometer for assessing the resting lips and the function, it has been found that the performance of lips tended to increase with age 35 .…”
Section: Discussionmentioning
confidence: 74%
“…With regard to age, the findings of this research showed lower pressure of the lips in older subjects. In the same vein, it was observed a decrease of pressure values with age in a study 34 that evaluated the tongue pressure with IOPI in subjects with malocclusion. In contrast, a sample of children in Class II has used a nozzle connected to a dynamometer for assessing the resting lips and the function, it has been found that the performance of lips tended to increase with age 35 .…”
Section: Discussionmentioning
confidence: 74%
“…The study included 55 healthy individuals between 18 and 55 years of age. For the sample calculation, the data obtained from measuring tongue pressure of 34 adults in a recent study was used as a reference ( 14 ) . Thus, considering a power of 80% and a significance level of 5%, the number of individuals for the present study should be at least 51 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Considerando as implicações acima descritas, nesse processo é fundamental que o fonoaudiólogo intervenha pré e pós cirurgia, com uma avaliação clínica criteriosa para compreender as condições anatômicas e funcionais do sistema estomatognático e seguir com o raciocínio clínico 13 .…”
Section: Métodounclassified
“…A organização da deglutição foi constatada, conforme os achados de estudos observados em pós operatório de curto período da intervenção 15,16,18,30 . Com relaçao à fala houve melhora na produção, principalmente com fricativos sibilantes, 13 sem queixas referentes a essa função.…”
Section: Considerações Finaisunclassified